2022
DOI: 10.3390/separations9070157
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of syn- and anti-3,5-Disubstituted Hydantoins by HPLC and SFC on Immobilized Polysaccharides-Based Chiral Stationary Phases

Abstract: The enantioseparation of syn- and anti-3,5-disubstituted hydantoins 5a–i was investigated on three immobilized polysaccharide-based columns (CHIRAL ART Amylose-SA, CHIRAL ART Cellulose-SB, CHIRAL ART Cellulose-SC) by high performance liquid chromatography (HPLC) using n-hexane/2-PrOH (90/10, v/v) or 100% dimethyl carbonate (DMC) as mobile phases, respectively, and by supercritical fluid chromatography (SFC) using CO2/alcohol (MeOH, EtOH, 2-PrOH; 80/20, v/v) as a mobile phase. The chromatographic parameters, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Enantiorecognition of trisubstituted rac - 6a – c and disubstituted marinoepoxides rac - 8a – c is based on attractive interactions such as π-π interactions, dipole-dipole interactions and hydrogen bonds, and repulsive interactions that are usually steric. Polar and π-π interactions between phenyl groups of the chiral stationary phase and the analyte play an important role in the chiral recognition mechanism [ 24 , 25 , 26 ] Based on numerous studies, it is difficult to predict which chiral selector of a particular stationary phase will separate the enantiomers of a compound, and which mobile phase will be the most favorable. The development of a good enantioselective chromatographic method requires finding the best combination of process parameters, described by chiral stationary phase selection, mobile phase composition and concentration, column temperature and back pressure (mainly for SFC) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enantiorecognition of trisubstituted rac - 6a – c and disubstituted marinoepoxides rac - 8a – c is based on attractive interactions such as π-π interactions, dipole-dipole interactions and hydrogen bonds, and repulsive interactions that are usually steric. Polar and π-π interactions between phenyl groups of the chiral stationary phase and the analyte play an important role in the chiral recognition mechanism [ 24 , 25 , 26 ] Based on numerous studies, it is difficult to predict which chiral selector of a particular stationary phase will separate the enantiomers of a compound, and which mobile phase will be the most favorable. The development of a good enantioselective chromatographic method requires finding the best combination of process parameters, described by chiral stationary phase selection, mobile phase composition and concentration, column temperature and back pressure (mainly for SFC) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, we have shown that DMC, an environmentally friendly solvent, can be efficiently used as a mobile phase in HPLC for the enantioseparation of synand anti-3,5-disubstituted hydantoins on the immobilized polysaccharide-based chiral stationary phases [22]. The CHIRAL ART Amylose-SA column was the most effective stationary phase, separating fourteen out of eighteen substituted hydantoins in non-standard mobile phase mode.…”
Section: Introductionmentioning
confidence: 99%